Ultrasound in preoperative assessment of pelvic and abdominal spread in patients with ovarian cancer: a prospective study - Fischerova, D; Zikan, M; Semeradova, I; Slama, J; Kocian, R; Dundr, P; Nemejcova, K; Burgetova, A; Dusek, L; Cibula, D (Ultrasound in obstetrics & gynecology, 2017)
OBJECTIVE: To analyze the accuracy of ultrasound in assessing pelvic and intra-abdominal spread in patients with ovarian cancer. METHODS: This prospective study enrolled all consecutive patients referred to a single gynecological oncology center for suspected ovarian cancer. We analyzed only data from patients with histologically confirmed primary ovarian cancer who were evaluated following predefined preoperative ultrasound, intraoperative and pathology protocols. We evaluated the agreement of depth of infiltration of the rectosigmoid wall, tumor spread in different peritoneal compartments and presence of metastatic retroperitoneal and inguinal lymph nodes, as determined at ultrasound, with intraoperative and histopathological findings. RESULTS: In total, 578 patients were enrolled between March 2008 and January 2013, of whom 394 met the study inclusion criteria and were analyzed; 74% of these suffered from advanced-stage cancer. Our results showed excellent agreement between ultrasound and histology in assessment of rectosigmoid wall infiltration (kappa value, 0.812; area under the receiver-operating characteristics curve, 0.898). The overall accuracy in evaluating different peritoneal compartments, retroperitoneal and inguinal lymph nodes and depth of rectosigmoid wall infiltration was 85.3%, 84.8%, 99.7% and 91.1%, respectively. Ultrasound showed high sensitivity only in the assessment of rectosigmoid wall infiltration (83.1%), peritoneal spread into the pelvis (81.4%) and omentum (67.3%), and inguinal metastatic lymph nodes (100%). The specificity of ultrasound in detection of all evaluated parameters was > 90%. CONCLUSION: This is the largest imaging study to date on ovarian cancer staging. Ultrasound can be used as the method of choice to plan rectosigmoid wall resection and dissection of infiltrated inguinal lymph nodes. In assessing different peritoneal and retroperitoneal compartments, ultrasound was accurate and highly specific. However, similar to other modern imaging techniques, it had relatively low sensitivity, further supporting the role of comprehensive surgical staging. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: těhotenství; Neoplasm Staging; Neoplasm Invasiveness; lidé; Middle Aged; Adult; Ovarian Neoplasms; diagnostic accuracy; imaging; ovarian cancer; prospektivní studie; staging; senzitivita a specificita; Female; Pelvis; ultrasound; Sensitivity and Specificity; ultrasonografie; Humans; nádory vaječníků; staging nádorů; břicho; Prospective Studies; Abdomen; lidé středního věku; Pregnancy; ženské pohlaví; pánev; Aged; invazivní růst nádoru; Preoperative Period; dospělí; Ultrasonography; předoperační období; senioři